Relative income shares - King, J. E.; Regan, Philip (London : Macmillan, 1976)
This book provides an introductory examination to current theories and empirical evidence concerning the distribution of national income between labour and property.
Includes bibliographical references: p. 81-[87]
osa;16/08/17
Loans
Keywords: Income distribution